Analisis Kekuatan Material Hasil Teknologi Fused Deposition Modelling Sebagai Material Alternatif Shoelast - Oktavian, Dicky; Prihadianto, Braam Delfian; Setyawan, Wawan Budi; Frannita, Eka Legya (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Pada industri alas kaki penggunaan shoelast merupakan aspek penting dalam proses manufaktur alas kaki. Dalam produksiMass, shoelast materials are generally made of wood, metal, or plastic which requires complex and high-costmanufacturing processes. For limited production needs, prototypes, or custom made materials require quite high costs andlong manufacturing process time. For limited production needs, alternative materials are needed that can be used asshoelast materials. This study aims to analyze the mechanical strength of the material produced by Fused DepositionModelling (FDM) technology as an alternative to shoelast making materials that are more flexible and efficient. The typesof materials used in this study are Polylactic Acid (PLA), Acrylonitrile Butadiene Styrene (ABS), and PolyethyleneTerephthalate Glycol (PETG). The three types of thermoplastic materials were printed with fill density variationparameters using a 3d printer and pressed testing was carried out. The data were analyzed by calculating the average valueand standard deviation of the compressive strength. The results showed that all materials have a compressive strengthhigher than 5 MPa, thus meeting the basic mechanical requirements as a shoelast material. Furthermore, PLA material hasthe characteristics that are suitable for making precise shoelast prototypes, but it is not suitable for repetitive lastingprocesses. While ABS material is more relevant for repetitive lasting processes and PETG material is relevant for limitedproduction but still requires durability